DEPRESSION TRAJECTORIES IN OLDER ADULTS: DIFFERENCES BY GENDER, RACE/ETHNICITY, EDUCATION, AND COHORT. (11th November 2018) - Abrams, L; Mehta, N
Abstract: Depression symptoms have been shown to follow a U-shaped curve over age. However, little is known about changes in the age trajectory of depression symptoms over time and differences by sociodemographic groups. We assessed the age trajectories of depression symptoms among older adults in a U.S. national sample, examining differences by gender, race/ethnicity, education, and cohort. Using the Health and Retirement Study, we analyzed data from 34, 675 adults aged 50 or older who were surveyed biennially between 1994 and 2014. Depression symptoms were measured via the 8-item Center for Epidemiological Studies Depression Scale. Multi-level models with random intercepts and slopes were used to characterize growth curves of depression over age, first adjusting for sociodemographic factors and then allowing each to modify the age effect. Adjusting for sociodemographics, mean depression symptoms at age 50 was 1.63, fell to a minimum of 1.34 at age 67, and then rose exponentially to a maximum of 2.61. Younger cohorts showed increasingly flat slopes (p<0.001), with declines over age in war babies (born 1942–1947) and early baby boomers (born 1948–1953). Women compared to men (p<0.001) had more depression symptoms with flatter slopes. All race/ethnicity groups and education levels showed similar curves over age. There is significant variability in the age trajectory of depression systems over time and by gender. The conventional U-shaped curve may not correctly characterize depression over old age for more recent cohorts. Studies are needed to understand the sources of this important shift in the age trajectory of depression symptoms.